Strategi Pengelolaan Kawasan Hutan Taman Nasional Kerinci Seblat (TNKS) Provinsi Jambi - Gerihano, Gerihano; K.P, Eka Intan; Simanjuntak, Sahat M.H. (Universitas Brawijaya, Indonesia, 2016)
Forest is place of living for many plants and animals. Moreover, forest is theÂ ecosystem support for living creature which directly live at the forest and surround it. ForestÂ is vulenarable resources to be exploited because generally in the forest is contained so manyÂ resources that have high economic value such as mineral. One of the areas that have a largeÂ forest in Jambi Province is TNKS. In fact, there are still illegal logging in TNKS that haveÂ been done by the people. If this issue happens continuously, it will make the forest in TNKSÂ area damage and will affected the people's life. Beside, the population's demand and economyÂ factors cause the forest becomes agricultural lands. In long terms, this condition will makeÂ the function of the forest as vegetation reduces as a result of clearing. Based on this condition,Â the study on the forest sustainable management of TNKS is necessary. This study aimsÂ to know how the forest sustainable management of TNKS is using the AHP method. The resultÂ shows that the most priority strategy that have to be concern is the law sanction based on the rulesÂ